Comparison of Acehnese Pidie Dialect Variations between Acehnese Nagan Raya Dialects of Acehnese People in Peukan Baro District - Nofiana S.; Putri Malahayati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research is entitled "Comparison of the Acehnese dialect of the Pidie dialect with the Nagan Raya dialect of Acehnese people in the Peukan Baro district". The formulation of the problem is,How do the variations of the Acehnese dialect of the Pidie dialect compare with the Acehnese dialect of the Nagan Raya in the Acehnese people of Peukan Baro District when interacting using the original speech of the two dialects. This researchaim to describe the comparison of variations in the Acehnese language found in the Acehnese dialect of Pidie with the Acehnese dialect of Nagan Raya, which is used by the Nagan Raya community who live in the Peukan Baro sub-district, when interacting using the native speech of the two regions. The method used in this study is a descriptive method with a qualitative approach. The main data source in this study is the Acehnese speaking community who live in Peukan Baro sub-district. Data was collected by using interview and documentation test techniques. The results of this study indicate that the comparison of language variations based on the usage spoken by the community: (1) comparative data of Acehnese language variations in the form of nouns; (2) comparative data of Acehnese language variations in the form of verbs; (4) comparative data on the variation of the Acehnese language in terms of speech belonging to customs, directions, and kinship calls.